Perumusan Strategi Bisnis pada PT SimpleFi Teknologi Indonesia (AwanTunai) dalam Menghadapi Persaingan Bisnis P2P Lending dengan Menggunakan Metode Analisis SWOT - Zefania Mikha Manurung; Sonja Andarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial technology or Fintech is one of the effects of technological advances in the financial sector, and one of them is P2P Lending. P2P lending is a joint funding fintech that provides financial services to bring together lenders and borrowers online. One of the companies that is operating in this business is AwanTunai. The P2P lending business has recently grown rapidly because it is in great demand by the public to get funding needs easily and instantly. Therefore, the purpose of this study is to formulate appropriate business strategy recommendations for AwanTunai in dealing with P2P lending business competition using the SWOT analysis method. The results obtained from this research indicate that the Strength-Opportunities (SO) strategy is the dominant SWOT strategy for AwanTunai, and the recommended strategy is to maintain low administrative costs at AwanTempo to continue being the preferred choice for customers amidst the increasing interest in online lending in Indonesian society.